2019
DOI: 10.3390/info10100300
|View full text |Cite
|
Sign up to set email alerts
|

When Personalization Is Not an Option: An In-The-Wild Study on Persuasive News Recommendation

Abstract: Aiming at granting wide access to their contents, online information providers often choose not to have registered users, and therefore must give up personalization. In this paper, we focus on the case of non-personalized news recommender systems, and explore persuasive techniques that can, nonetheless, be used to enhance recommendation presentation, with the aim of capturing the user’s interest on suggested items leveraging the way news is perceived. We present the results of two evaluations “in the wild”, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 53 publications
2
18
0
1
Order By: Relevance
“…The ad populum, on the other hand, does not seem to have any efficacy. As anticipated above, this datum is compliant with other findings exploited in the context of persuasive news and e-commerce item recommendations [ 33 ]. As a consequence, this technique could be probably left aside in future works since it does not seem to work properly when employed within technological artifacts.…”
Section: Discussion and Future Worksupporting
confidence: 89%
“…The ad populum, on the other hand, does not seem to have any efficacy. As anticipated above, this datum is compliant with other findings exploited in the context of persuasive news and e-commerce item recommendations [ 33 ]. As a consequence, this technique could be probably left aside in future works since it does not seem to work properly when employed within technological artifacts.…”
Section: Discussion and Future Worksupporting
confidence: 89%
“…These include using visuals to increase item salience, item re-ranking, and setting defaults. For news recommendation specifically, Gena et al (2019) found that nudges based on giving users the idea certain items were popular were not effective, while negative framing (nudging users to consume certain news items because of limited availability) was. The authors argue that future work should address which types of nudges are ethically acceptable in the area of persuasive technologies.…”
Section: Nudgingmentioning
confidence: 99%
“…Recommender systems are systems with the ability to provide suggestions or to direct a user to a service, product, or content, with the aim of maximizing the personal interest. Decades of research have produced multiple recommendation algorithms [6], mechanisms for evaluating their effectiveness, including user studies [7], online evaluations A/B tests and offline evaluations [8], and user interfaces and experiences to embody them [9]. Today, the interest in this area still remains high and current most highly rated Internet sites as Amazon, eBay, or YouTube use recommender systems as part of the services they provide to their subscribers.…”
Section: Recommender Systemsmentioning
confidence: 99%